POTENSI KEPARIWISATAAN DI PULAU KARAKELONG, SULAWESI UTARA - Vita Vita (Balai Arkeologi Yogyakarta, 2012)
Karakelong island located in the Talaud Islands, North Sulawesi Province. In astronomy Talaud Islands lies between 3° 45'- 5° north latitude and between 126° 30' - 126°45' east longitude. The island is surrounded by natural beauty of the sea coast and forests. Archaeological remnants from this island among others are a series of Karakelong caves, one of which is the Balangingi cave. From this site has been obtained more than 2.604 fragments of pottery, three red-glass beads and two green-glass beads, two fragments of bronze/copper and a segment of bronze/copper bracelets. Radio carbon dating on charchoal samples found at the depth of 20-30 cm showed the date of 950 ± 130 BP in the middle layer of the culture. (Tanudirjo 2001). From observations made on the vegetation environment in Karakelong island, in particular in the sub distrct of Rainis (Rainis village), the physiognomy of plants can be divided in to the environment of coastal vegetation, plantation environment, bush and jungle environments. This site could be expected to be come a tourist destination in the future, considering the site has the potential for archaeological remains as well as its potential environment.